The influence of the design of mandibular major connectors on gingival health (2014)
Background: The objective of this study was to assess the influence of lingual bar and lingual plate major connectors on plaque retention and gingival health among patients who presented in University College Hospital (UCH), Ibadan, Nigeria. Methods: This comparative intervention study was carried out among fifteen patients aged 28 to 60 years with Kennedy class III lower edentulous arch. Two metal dentures with different major connector designs (lingual plate and lingual bar) were fabricated for each patient. After professional scaling and polishing, a baseline score of the oral hygiene was done using the plaque index of Sillness and Loe and the gingival health using the gingival index of Loe and Sillness. Each patient was randomly assigned either a denture with the plate or bar design to use for three months and then recalled for reassessment of oral hygiene and gingival health. Professional scaling and polishing was done post removal and a new baseline assessment of oral hygiene and gingival health recorded. The dentures were now exchanged and the second major connector design inserted. Each patient was recalled for reassessment of the oral hygiene and gingival health after three months. The level of plaque accumulation and gingival inflammation with the use of lingual plate and bar dentures were determined and compared. Results: There was no statistically significant difference in the mean plaque index score for the lingual bar design at three months and the mean plaque index score at three months for the lingual plate (p>0.05). However, a statistically significant lower mean gingival index score was noted three months post insertion for lingual bar designs when compared to plate designs. Conclusion: Within the limitation of this study, better gingival health was noted with the bar designs when compared with the plate designs.